An importance performance analysis of performance dimensions in public hospitals. (1st January 2014) - Ellangovan, K.; Prakash Sai, L.; Kamalanabhan, T.J.
The purpose of this paper is to understand physicians' perspectives on performance dimensions in public hospitals in the state of Kerala and to identify critical areas of concern. A survey was conducted in 23 district hospitals using an instrument developed on Likert's scale. Responses were obtained on the perceived 'importance' and actual 'performance' of the identified dimensions. Importance performance analysis (IPA) conducted on the data brought into focus, several areas of functioning of public hospitals wherein, both managerial and policy interventions are required. Functioning of the intensive care unit (ICU), casualty, adequate beds, autonomy, uninterrupted supply chain and availability of funds were some of the governance issues that needed urgent remedial action. Redressing these issues will increase the motivation of physicians leading to better clinical outcomes. The findings argue well for major administrative and policy interventions. Further, this would strengthen the argument for more funds for health sector within the government.